PENGARUH STRUKTUR MODAL, STRUKTUR AKTIVA DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN DENGAN SUKU BUNGA SEBAGAI VARIABEL MODERASI PADA PERUSAHAAN SUB SEKTOR INDUSTRI MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Ivan Marcellino; Jonnardi (Fakultas Ekonomi Universitas Tarumanagara, 2025)
The purpose of this research was to determine The Influence of Capital Structure, Asset Structure and Profitability on Company Value with Interest Rates as a Moderating Variable in Food and Beverage Industry listed on the Indonesian Stock Exchange. The method used in this research uses systematic random sampling and using 72 companies as population and processed using E-views 12.0. The results of the research show that there is no influence of Capital Structure, Asset Structure, Profitability and Interest Rates on Company Value. Interest Rates are not able to moderate Capital Structure on Company Value, Interest Rates moderate Asset Structure and Profitability on Company Value.